Edapho-climatic Characteristics of Precarpathian Biotopes in Participation of Cenopopulation of Polygonatum MILL. Species - Nadiya Riznychuk; Viktoriya Hniezdilova (Vasyl Stefanyk Precarpathian National University, 2022)
The territory of research on landscape-geographical zoning is confined to the Precarpathians - part of the Western Ukraine, within the Lviv, Ivano-Frankivsk and Chernivtsi regions (Kravchuk, 1999). It stretches a relatively narrow strip between the Dniester valley and the northeastern foothills of the Ukrainian Carpathians (Koinov, 2014). Coenopopulations of four species of the genus Polygonatum Mill (Polygonatum multiflorum (L.) All., Polygonatum odoratum (Mill.) Druce., Polygonatum verticillatum (L.) All., Polygonatum latifolium Desf.) were studied within the seven territorial divisions of the Precarpathian region. We studied these species at 59 research sites dedicated to 14 types of habitats (Didukh, 2011). The studied biotopes of the Precarpathian region are characterized by a number of edaphic and climatic indices. The humus content is 1.94-2.98 %, reaching the maximum values in the biotopes of the Pokutsk hills, and the minimum - in the Kalush (Limnitsko - Bolokhiv) basin. The average soil solution response rates are very acidic within the Storozhynets strand (pH (saline) - 4.33 units); strongly acidic level - within the Kalush and Stanislav basin and Pokuttia height (pH (salt) - 4.68; 4.82 and 4.76 units, respectively); slightly acidic level - within the Upper Dniester Basin and Voynylivskyi hills (pH (salt) - 5.34) and Chernivtsi hills (pH (salt) - 5.05). The moisture content, the amount of active temperatures and the level of illumination vary greatly depending on the type of biotope. The soils of wetland alder habitats are characterized by maximum moisture content (> 40%) and the minimum - the biotopes along the highways and abandoned pastures (<20 %). The sum of active temperatures at a depth of 20 cm is highest in non-forested areas with a low degree of loosening. The minimum level of illumination (in the range of 760 - 900 lux) was stated in forest biotopes, the maximum (> 2000 lux) was found in biotopes of abandoned pastures and hay meadows. Soils within the studied Precarpathian biotopes are characterized by low and medium supply of N, P and high content of K. The weighted average value of mobile phosphorus varies from 39.49 mg / kg in the biotopes of the Kalush Basin to 81.18 mg / kg in the biotopes of the Chernivtsi Upland; of hydrolyzed Nitrogen - from 68.07 in the biotopes of the Kalush Basin to 83.93 - Storozhynets Strand. The highest weighted average values of mobile potassium content were found within the Pokuttia Upland (150.70 mg/kg), the lowest - the Voynyliv Upland (84.1 mg/kg).